The factors influencing waste management for economic development—the perspective of Nelson Mandela bay municipality residents - Mngomezulu, Sibongangani; Mbanga, Sijekula; Adeniran, Adeleye (Frontiers in Sustainability, 2024)
The rapid increase in volume and variety of solid waste as a result of continuous economic growth, urbanization, and industrialization has become an intractable problem for the public and private sectors, making it difficult to ensure effective and sustainable waste management. The study sought to understand the perspective of Nelson Mandela Bay Municipal residents on their perceived influence of municipal waste management on economic development. The study used a quantitative techniques approach, with a structured questionnaire. Data was collected from 255 respondents. The quantitative question aimed to determine if the influence was positive or negative, and the Likert scale question had a scale of 1 to 5. This research identified various types of waste, assessed challenges, and evaluated waste's potential for resource creation. The study concluded that municipal waste includes organic, paper, plastic, metal, glass, food, garden, hazardous, construction, demolition, and nonrecyclable waste. Environmental pollution is a major challenge, and 26 factors positively influence waste to wealth. waste to wealth can be achieved through social behavior, education/knowledge, MSWM governance, and economic feasibility for MSWM. The research also highlighted the importance of land attributes, budget allocation, trained personnel, and government regulations. The framework proposed aims to minimize urban poverty while preserving the environment and supporting the present urban economy. Urban communities can utilize solid waste management as a mechanism to foster economic develop ment. The fundamental question is whether stakeholders will continue to ignore waste's potential demands and benefits for urban economic growth.